Unfavorable Outcomes Related to Endovascular Treatment of Giant Vertebrobasilar Aneurysms - Li, Miao; Liang, Huaxin; Wang, Jie (Frontiers in Neurology, 2020)
Background Giant vertebrobasilar aneurysms (GVBAs) have an unfavorable natural history if left untreated and often pose a sizeable challenge to endovascular treatment. The aim of this study was to analyze the angiographic and clinical outcomes of GVBAs treated by various endovascular procedures. Methods Between January 2010 and September 2018, 27 patients with 27 GVBAs treated endovascularly were enrolled in this consecutive study. The clinical and angiographic features, treatment modalities, and outcomes were analyzed. Results The patient cohort comprised 21 men (77.8%) and 6 women (22.2%) of mean age 42.7 ± 18.9 years (range, 6–65 years). The most common presenting symptom was compressive symptoms, present in 15 patients (55.6%). None of the GVBAs was ruptured. Of the 27 GVBAs, 23 aneurysms were dissecting aneurysm with intramural hematoma and 4 aneurysms were saccular. Regarding treatment approach, internal trapping was used in 5 aneurysms, stent-assisted coil embolization in 10, sole stenting in 4, and flow diverters in 8. Overall, 12 patients (44.4%) had an unfavorable angiographic or clinical outcome: 3 patients presented with postoperative complications and subsequent death, and 9 with poor prognosis during follow-up. Conclusions Patients with GVBAs may not benefit from endovascular treatment. Newer-generation devices are necessary to provide more optimal therapy for the management of these complex lesions.